Recurrent De Novo NAHR Reciprocal Duplications in the ATAD3 Gene Cluster Cause a Neurogenetic Trait with Perturbed Cholesterol and Mitochondrial Metabolism. - Gunning, Adam C; Strucinska, Klaudia; Muñoz Oreja, Mikel; Parrish, Andrew; Caswell, Richard; Stals, Karen L; Durigon, Romina; Durlacher-Betzer, Karina; Cunningham, Mitchell H; Grochowski, Christopher M; Baptista, Julia; Tysoe, Carolyn; et al. (Am J Hum Genet, 2020)
Recent studies have identified both recessive and dominant forms of mitochondrial disease that result from ATAD3A variants. The recessive form includes subjects with biallelic deletions mediated by non-allelic homologous recombination. We report five unrelated neonates with a lethal metabolic disorder characterized by cardiomyopathy, corneal opacities, encephalopathy, hypotonia, and seizures in whom a monoallelic reciprocal duplication at the ATAD3 locus was identified. Analysis of the breakpoint junction fragment indicated that these 67 kb heterozygous duplications were likely mediated by non-allelic homologous recombination at regions of high sequence identity in ATAD3A exon 11 and ATAD3C exon 7. At the recombinant junction, the duplication allele produces a fusion gene derived from ATAD3A and ATAD3C, the protein product of which lacks key functional residues. Analysis of fibroblasts derived from two affected individuals shows that the fusion gene product is expressed and stable. These cells display perturbed cholesterol and mitochondrial DNA organization similar to that observed for individuals with severe ATAD3A deficiency. We hypothesize that the fusion protein acts through a dominant-negative mechanism to cause this fatal mitochondrial disorder. Our data delineate a molecular diagnosis for this disorder, extend the clinical spectrum associated with structural variation at the ATAD3 locus, and identify a third mutational mechanism for ATAD3 gene cluster variants. These results further affirm structural variant mutagenesis mechanisms in sporadic disease traits, emphasize the importance of copy number analysis in molecular genomic diagnosis, and highlight some of the challenges of detecting and interpreting clinically relevant rare gene rearrangements from next-generation sequencing data.
Keywords: Amino Acid Sequence; ATPases Associated with Diverse Cellular Activities; Brain Diseases; Cardiomyopathies; Cholesterol; Corneal Opacity; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Homologous Recombination; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Diseases; Mitochondrial Proteins; Muscle Hypotonia; Mutation; Protein Conformation; Seizures; Sequence Homology

KIF5A mutations cause an infantile onset phenotype including severe myoclonus with evidence of mitochondrial dysfunction. - Duis, Jessica; Dean, Shannon; Applegate, Carolyn; Harper, Amy; Xiao, Rui; He, Weimin; Dollar, James D; Sun, Lisa R; Waberski, Marta Biderman; Crawford, Thomas O; Hamosh, Ada; Stafstrom, Carl E (Ann Neurol, 2016)
Missense mutations in kinesin family member 5A (KIF5A) cause spastic paraplegia 10. We report on 2 patients with de novo stop-loss frameshift variants in KIF5A resulting in a novel phenotype that includes severe infantile onset myoclonus, hypotonia, optic nerve abnormalities, dysphagia, apnea, and early developmental arrest. We propose that alteration and elongation of the carboxy-terminus of the protein has a dominant-negative effect, causing mitochondrial dysfunction in the setting of an abnormal kinesin "motor." These results highlight the role of expanded testing and whole-exome sequencing in critically ill infants and emphasize the importance of accurate test interpretation. Ann Neurol 2016;80:633-637.
Keywords: Apnea; Child, Preschool; Deglutition Disorders; Developmental Disabilities; Fatal Outcome; Female; Frameshift Mutation; Humans; Infant; Kinesins; Male; Mitochondrial Diseases; Muscle Hypotonia; Mutation; Myoclonus; Optic Nerve

MECR Mutations Cause Childhood-Onset Dystonia and Optic Atrophy, a Mitochondrial Fatty Acid Synthesis Disorder. - Heimer, Gali; Kerätär, Juha M; Riley, Lisa G; Balasubramaniam, Shanti; Eyal, Eran; Pietikäinen, Laura P; Hiltunen, J Kalervo; Marek-Yagel, Dina; Hamada, Jeffrey; Gregory, Allison; Rogers, Caleb; Hogarth, Penelope; et al. (Am J Hum Genet, 2016)
Mitochondrial fatty acid synthesis (mtFAS) is an evolutionarily conserved pathway essential for the function of the respiratory chain and several mitochondrial enzyme complexes. We report here a unique neurometabolic human disorder caused by defective mtFAS. Seven individuals from five unrelated families presented with childhood-onset dystonia, optic atrophy, and basal ganglia signal abnormalities on MRI. All affected individuals were found to harbor recessive mutations in MECR encoding the mitochondrial trans-2-enoyl-coenzyme A-reductase involved in human mtFAS. All six mutations are extremely rare in the general population, segregate with the disease in the families, and are predicted to be deleterious. The nonsense c.855T>G (p.Tyr285), c.247_250del (p.Asn83Hisfs4), and splice site c.830+2_830+3insT mutations lead to C-terminal truncation variants of MECR. The missense c.695G>A (p.Gly232Glu), c.854A>G (p.Tyr285Cys), and c.772C>T (p.Arg258Trp) mutations involve conserved amino acid residues, are located within the cofactor binding domain, and are predicted by structural analysis to have a destabilizing effect. Yeast modeling and complementation studies validated the pathogenicity of the MECR mutations. Fibroblast cell lines from affected individuals displayed reduced levels of both MECR and lipoylated proteins as well as defective respiration. These results suggest that mutations in MECR cause a distinct human disorder of the mtFAS pathway. The observation of decreased lipoylation raises the possibility of a potential therapeutic strategy.
Keywords: Basal Ganglia; Cells, Cultured; Child; Child, Preschool; Dystonic Disorders; Fatty Acids; Female; Fibroblasts; Genetic Complementation Test; Humans; Infant; Male; Mitochondria; Mitochondrial Diseases; Models, Molecular; Mutation; Mutation, Missense; Optic Atrophy; Oxidoreductases Acting on CH-CH Group Donors; Pedigree; RNA Splice Sites; Saccharomyces cerevisiae